HEALTH FACILITIES LOCATIONAL ANALYSIS IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE-NIGERIA USING GIS APPLICATION - Oboh Satur Okosun (Geosfera Indonesia, 2018)
The most important indices of defining general welfare and quality of life of people in the world are the physical and mental health of individuals. This study attempts to examine GIS solution in the spatial analysis of health facilities in Makurdi local government area of Benue State, through mapping of the existing health facilities located in the study area, their spatial distribution pattern, identify areas with marginal services and propose a model for the future development as well examine the availability and accessibility of the existing health facilities, e.g (road network, travel time, distance covered and queuing time). Theâ€ Nearest neighbour analysisâ€ Geospatial statistical method was employed to determine the spatial distribution pattern of the existing health facilities in other to determine the area of limited service and accessibility to healthcare facilities. The findings indicated that the healthcare facilities are randomly distributed; Fiidi ward was discovered to have limited service as regards the healthcare facilities in the study area. In line with the findings, recommendations were made on the use of GIS to build a concept that can be followed and replicated in divergent social-economic and political contexts. Conclusively, the study had shown that GIS is a vital tool in healthcare facility analysis and also in live application issues and thus should be encouraged in Nigeria for national economic transformation and sustainable development. keywords: Health, GIS, Mapping, Location References Ajala, O.A., Sanni, L., and Adeyinka, S.A.,(2005).Accessibility to Healthcare Facilities: APanacea for Sustainable Rural Development in Osun State, South western Nigeria.Journalof Human Ecology,18(2):121â€“128. Amer, S., (2007).Toward Spatial Justice in Urban Health Services Planning. PhD.Dissertation,ITC,Enschede, The Netherlands. Atser J.,and Akpan, P.A.,(2009).Spatial Distribution and Accessibility of Health Facilities inAkwa Ibom State, Nigeria.Ethiopian Journal of Environmental Studies and Management(EJESM)Vol.2 (2):pp. 49-57. Fagbeja,M.A.,(2000).Mapping the Incidences of Chronic Bronchitis and BronchopneumoniaandVerification ofHigh-RiskAreas Using GIS.M.Sc.Dissertation,Universityof Ibadan,Ibadan,Nigeria. Fanan,U.,and Felix,K.(2014).Analysis of the Spatial Distribution of Health Facilities inBenue State, Nigeria,Public Health Research2014, 4(5): 210-218.DOI:10.5923/j.phr.20140405.09Ogundare, E.I.,(1982).Healthcare Delivery is a success in Oyo State.p.7October 27,DailySketch,Lagos-Nigeria. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License